The Economics and Politics of Socialism. - Brus, Wlodzimierz (Taylor and Francis, 2013)
The volume focuses on the socio-political aspects of economic transformations in the Eastern European Socialist countries. Particular emphasis is laid on the problem of interrelations between the plan and the market and between economic incentives and social consumption. The volume also examines economic and political factors in the wider political context, particularly looking at the question of democratization within industry and politics.